Model Pemulihan Ekonomi Berbasis Komunikasi Pembangunan bagi Masyarakat yang Terkena Bencana di Kawasan Obyek Wisata Pantai - eni nur aeni (Jurnal Ilmu Komunikasi Acta Diurna, 2011)
There are a lot of difference policies for regional governments in Cilacap and Bantul afterearthquake and tsunami on July, 17 2006. Cilacap government didn’t give any programs to recovereconomical situation to their people except rebuild facilities around tourism at Widarapayungbeach. Also in Bantul government, there is not program for to recover tourism activities becausethere thougt that they have not any victims in that tsunami at Parang Tritis beach. Although theygave relocation program to their people but the program was not purposed to recover after tsunami.They had a plan to relocate trade location before the tsunami was coming. The most reason torelocate for people trading was to rearrange old location to new one and make the beach wasshown clean and comfort for tourism acitivities. It is different if it’s compare to Ciamis governmentpolicy to give recovery programs for their people at Pangandaran Beach. The programswere used to recovery tourism activities. In earlier program, people participation was involved bygovernment. They were participated in economical recovery program planning. However largelypeople in Pangandaran feel this recovery programs although they are not participated in implementationphase. From this data, it is too difficult to try the economical recovery program as amodel at Pangandaran beach to Widarapayung beach and Parang Tritis beach. This researchused qualitative method with indepth interview and observation to collect data.